Pengaruh Sistem Pelaporan dan Pengendalian Akuntansi Terhadap Efektifitas Sistem Pengendalian Manajemen (Studi Pada Fakultas-Fakultas Dalam Lingkungan Universitas Muhammadiyah Aceh) - Yusliana Yusliana; Nadirsyah Nadirsyah (Jurnal Telaah dan Riset Akuntansi, 2017)
This study aimed to examine empirically the effect of reporting and accounting control system of the effectiveness of management control systems on the faculties of the University of Muhammadiyah in Aceh Province, either simultaneously or partially. The population in this study were 70 respondents consisting of leaders and governors at the level of Rectorate and Faculty. Sources of data used were primary data that was being done through a questionnaire delivered directly. Data analysis method used was multiple linear regression analysis. The results showed that the reporting and accounting control system affected the effectiveness of the management control system either and partially on the faculties of the University of Muhammadiyah  in Aceh. Thus, all the results of this thesis supported the proposed hypothesis.KEYWORDS : Reporting System, Accounting Control, Effectiveness, and  Management Control System